2020
DOI: 10.3389/fphar.2020.00628
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Neurobiology and Pharmacology of GPR12

Abstract: GPR12 is a G protein-coupled orphan receptor genetically related to type 1 and type 2 cannabinoid receptors (CB 1 and CB 2 ) which are ancient proteins expressed all over the body. Both cannabinoid receptors, but especially CB 1 , are involved in neurodevelopment and cognitive processes such as learning, memory, brain reward, coordination, etc. GPR12 shares with CB 1 that both are mainly expressed into the brain. Regrettably, very little is known about physiology of GPR12. Concerning its pharmacology, GPR12 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 86 publications
(141 reference statements)
0
15
0
Order By: Relevance
“…In addition to the two well-characterized G protein-coupled receptors CB1 and CB2, several orphan G protein-coupled receptors or GPRs have been described in the last years to be putative cannabinoid receptors, such as GPR3, GPR6, GPR12, GPR18, and GPR55 [ 173 , 174 , 175 ]. GPR3, GPR6, and GPR12 have a close phylogenetic affinity and conserve specific sequences with the cannabinoid receptors CB1 and CB2 [ 173 ].…”
Section: The Orphan G Protein-coupled Receptors (Gprs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the two well-characterized G protein-coupled receptors CB1 and CB2, several orphan G protein-coupled receptors or GPRs have been described in the last years to be putative cannabinoid receptors, such as GPR3, GPR6, GPR12, GPR18, and GPR55 [ 173 , 174 , 175 ]. GPR3, GPR6, and GPR12 have a close phylogenetic affinity and conserve specific sequences with the cannabinoid receptors CB1 and CB2 [ 173 ].…”
Section: The Orphan G Protein-coupled Receptors (Gprs)mentioning
confidence: 99%
“…An increased hippocampal expression was also observed for GPR6 in the 3 × Tg AD mouse model, where GPR6 modulates the neuroprotective effect of the complement protein C1q against Aβ [ 180 ]. GPR18 and GPR55 despite, GPR3, GPR6, and GPR12, have low homology with CB1 and CB2 [ 175 ]. GPR55 has opposite signaling pathways from CB1/CB2 since it is coupled to Gα 12,13 , and its activation is linked to an outflow of calcium from intracellular stores via phospholipase C [ 181 ].…”
Section: The Orphan G Protein-coupled Receptors (Gprs)mentioning
confidence: 99%
“…These observations clearly demonstrated that GPR12 could inhibit the migration of Eca109 and FaDu cells through inhibiting EMT progression, although the underlying mechanism remained to be elucidated. There have been numerous studies on GPR12 in neurology, 26 however, few such studies focus on tumors. Our research shows that GPR12 could be a potential therapeutic target for regulating EMT and cancer migration.…”
Section: Discussionmentioning
confidence: 99%
“…Other putative receptors strongly associated with the endocannabinoid system (e.g., GPR12, GPR18, and GPR55) have also been associated with multiple cognitive processes such as learning and memory and food intake. [183][184][185][186][187][188].…”
Section: Cannabismentioning
confidence: 99%